Pengelolaan Sistem Informasi PAIS ON THE SPOT: Inovasi Dan Dampak Dalam Peningkatan Kualitas Layanan di Seksi PAIS Kantor Kementrian Agama Kota Surabaya - Thohir, Muhammad; Nova, Nova Auliyatul Faizah; Mardiyah (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2024)
This study aims to examine the management of the PAIS ON THE SPOT information system in improving the quality of service in the PAIS section of the Ministry of Religion Office of Surabaya City. This study uses a qualitative method with a descriptive approach, data obtained through interview techniques, observation and documentation. The results of the study indicate that the management of the PAIS ON THE SPOT information system in the PAIS section is quite good starting from planning, organizing, implementing, and supervising. However, in organizing there is no division of tasks between employees, but this does not become a barrier to management. Improvement efforts made by the PAIS section through this system by upgrading the PAIS ON THES SPOT information system to the official WhatsApp and improving the existing menu features by combining PAIS ON THES SPOT with the SIAGA and EMIS applications so that there is no need to respond manually, just through auto response. Human resources are a supporting and inhibiting factor. The human resources who operate this information system have mastered information technology, while the inhibitors are still some GPAI human resources, especially those who are a little older, who have difficulty using it.